The Discernment of the Deceits of the Devil in angelum lucis according to St. Ignatius of Loyola and St. John of the Cross - Juan Manuel Rossi (Polonia Sacra)
The discernment of motions in the soul is raised, from the dawn of the Church, as a first necessity for the spiritual life. Motions that come from God pass through our soul, but there are also tendencies that are born of our own nature, and there are others that are suggested to us by the devil, whom St. Ignatius calls “the enemy of human nature”. It is therefore urgent to learn to discern where the different motions come from, to support them, or to combat them. In this field, because of its particular difficulty, special attention should be paid to the deceptions of the devil “sub angelo lucis”, that is, those who are under the appearance of good or virtue. St. Ignatius of Loyola, in his Spiritual Exercises, gives fundamental Rules in this regard, and in other meditations helps to understand the need to clarify the thought and rectify the intention. St John of the Cross in his works completes this Ignatian reflection on the confusion created by the devil “sub angelo lucis”.